PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA PHYMAGZ UNTUK MENINGKATKAN HASIL BELAJAR FISIKA - Rika Anggraeni; M. Nor M. Nor; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine the increase in physics learning outcomes class XI SMAN 3 Dumai using problem based learning model with Phymagz media. The form of this study was Quasi Experimental Design with Nonequivalent Control Group Design. The sample of research is student of XI MIPA3 as experiment class and class XI MIPA2 as control class. Instrumen of data collection is the result of cognitive learning given to the sample before and after the learning. Data analysis techniques used are descriptive and inferential anaysis. The result showed the students average absorption by applying problem based learning model with phymagz media is higher than the application of conventional learning. Thus concluded that the application of learning problem based learning model with phymagz media can improve student learning outcomes in learning physics in static fluid in class XI MIPA SMAN 3 Dumai.Keywords: Problem Based Learning, Physics Magazine, Learning Outcomes.